Conceptualizing work and organizational values from the Islamic perspective - Nur Atiqah Abdullah,; Fatimah Omar,; Nik Mutasim Nik Ab. Rahman,; Khairul Akmaliah Adham, (Penerbit Universiti Kebangsaan Malaysia, 2013)
Literature suggests the importance of values in influencing one’s affective and cognitive processes, which in turn, affect his or her behaviour. In this regard, values are fundamental in directing an individual’s motivation toward work and supporting the formation of positive attitudes, which then influence his or her actions and decision making. The objective of this study is to provide a model that links basic values to work values and organizational values. The paper first presents the general concept of values, work values, and organizational values from the western literature. It then analyses these conceptualizations against the concepts drawn from the Islamic principles and traditions. The study found that the Islamic perspective views values as manifested from one’s worldview, which is based upon divine principles. Moreover, individual and organizational values are developed and fostered through two authentic sources, the Holy Quran and the Hadith. Individuals and organizational conducts are aimed at achieving worldly and superordinate goals of getting rewards from Allah SWT. Conversely, discussions on the concept of values in Western literature generally separate values from a person’s religion and deeply held belief, while organizational values are generally derived from the founders’ desire to institutionalize their firms.